2014
DOI: 10.1371/journal.pone.0096501
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted Knockdown of IQGAP1 Inhibits the Progression of Esophageal Squamous Cell Carcinoma In Vitro and In Vivo

Abstract: IQGAP1 is a scaffolding protein that can regulate several distinct signaling pathways. The accumulating evidence has demonstrated that IQGAP1 plays an important role in tumorigenesis and tumor progression. However, the function of IQGAP1 in esophageal squamous cell carcinoma (ESCC) has not been thoroughly investigated. In the present study, we showed that IQGAP1 was overexpressed in ESCC tumor tissues, and its overexpression was correlated with the invasion depth of ESCC. Importantly, by using RNA interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
7
30
0
Order By: Relevance
“…A previous study showed that IQGAP1 knockdown results in a prominent reduction in cell proliferation and invasion in the FTC133 cells 15. As is reported in some other types of cancers,21,22 we also found that knockdown of IQGAP1 suppressed proliferation of SW579 and TPC-1 cell lines and reduced tumor growth in vivo. To explore how IQGAP1, as a multifunctional protein, regulates tumor proliferation and EMT in thyroid cancer, the regulation of IQGAP1 on the expressions of the EMT-related proteins E-cadherin, N-cadherin, Vimentin, Twist1, β-catenin and the Wnt/β-catenin targets c-myc and cyclin D1 in thyroid cancer were detected in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study showed that IQGAP1 knockdown results in a prominent reduction in cell proliferation and invasion in the FTC133 cells 15. As is reported in some other types of cancers,21,22 we also found that knockdown of IQGAP1 suppressed proliferation of SW579 and TPC-1 cell lines and reduced tumor growth in vivo. To explore how IQGAP1, as a multifunctional protein, regulates tumor proliferation and EMT in thyroid cancer, the regulation of IQGAP1 on the expressions of the EMT-related proteins E-cadherin, N-cadherin, Vimentin, Twist1, β-catenin and the Wnt/β-catenin targets c-myc and cyclin D1 in thyroid cancer were detected in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…IQGAP1 is upregulated in several different types of cancers [52], including hepatocellular [53,54], prostate [55], glioma [56] and breast [57] cancers. In most studies, perturbing IQGAP1 levels by upregulation or downregulation has a corresponding effect on cell migration in a variety of normal and cancer cell lines [55][56][57][58]. It was also seen that IQGAP1 promotes cell migration in an interdependent manner with PIPKIγ.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP1 knock out animals show no obvious developmental defects but exhibit gastric hyperplasia [114] and reduced tumorigenesis [115]. Silencing IQGAP1 in cell lines also seems to inhibit their cancerogenic behavior [109,116].…”
Section: Figure 6 a Schematic View Of Iqgap1 Domains And Examples Ofmentioning
confidence: 99%